Investigating Factors that Influence Māori Boys as They Construct their Māori Identity - Hema, Joshua (Curtin University, 2020)
The study used Kaupapa Maori and Interpretive Phenomenological Analysis (IPA) to investigate Maori identity. It used semistructured interviews to gather information from 12 Maori boys at one New Zealand high school.  The results indicated that various factors influenced Maori identity, including; the influence of Maori grandparents; whanau (extended family); upbringing; negative stereotyping of Maori; and, being excluded by other Maori. The findings have various implications for education in New Zealand schools.